EXERCISE TESTING IN THE ASSESSMENT OF CHRONIC CONGESTIVE HEART FAILURE - Lainchbury, John G; Richards, A Mark (Heart (British Cardiac Society), 2002)
Exercise testing in assessing CHF: key points [black right triangle] Exercise testing with monitoring of gas exchange parameters provides useful information on exercise capacity and prognosis in heart failure; in addition it is helpful in establishing the cause of exercise limitation [black right triangle] Both treadmill and bicycle protocols are acceptable, but attention to technical aspects of exercise testing are important in order to obtain maximum exercise data [black right triangle] Peak V* o 2 is probably the strongest predictor of prognosis in heart failure but other exercise, clinical, and hormonal data must be taken into account in arriving at an assessment of prognosis. [black right triangle] In subjects unable to perform a maximal exercise test submaximal data such as the slope of the relation between V*E and V* co 2 may be useful [black right triangle] Further studies of the response of neurohormones to exercise may add to the utility of exercise tests in assessing prognosis We have undertaken a study in 68 patients with NYHA class III-IV heart failure and average pV* o 2 of 13.6 ml/kg/min. [...]preliminary data suggest combining maximum exercise testing with assessment of neurohormones (particularly the natriuretic peptides both at rest and at peak exercise) may be valuable.